2020
DOI: 10.21203/rs.3.rs-40874/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enolase 1 Regulates Stem Cell-Like Properties in Gastric Cancer Cells by Stimulating Glycolysis

Abstract: Abstract Background: Recent studies have demonstrated that gastric cancer stem cells (CSCs) are a rare sub-group of gastric cancer (GC) cells and play an important role in promoting the tumor growth and progression of GC. In the present study, we demonstrated that the glycolytic enzyme Enolase 1 (ENO1) was involved in the regulation of the stem cell-like characteristics of GC cells.Methods: Self-renewal, Chemosensitivity and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Moreover, PGK1 is a kinase involved in oncogenic signaling, thus understanding the processes driven by DNA-PK/PGK1 interaction may identify novel mechanisms that drive proliferation and metastasis. Lastly, ENO1 is a glycolytic enzyme that has been shown to contribute to proliferation, metastasis and therapy resistance through its role in glycolysis [45]. ENO1 is overexpressed and promotes tumor growth in head and neck, hepatocellular and gastric cancers [45].…”
Section: Combination Of Dna-pk and Glycolysis Inhibitor Decreases Proliferation In Crpcmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PGK1 is a kinase involved in oncogenic signaling, thus understanding the processes driven by DNA-PK/PGK1 interaction may identify novel mechanisms that drive proliferation and metastasis. Lastly, ENO1 is a glycolytic enzyme that has been shown to contribute to proliferation, metastasis and therapy resistance through its role in glycolysis [45]. ENO1 is overexpressed and promotes tumor growth in head and neck, hepatocellular and gastric cancers [45].…”
Section: Combination Of Dna-pk and Glycolysis Inhibitor Decreases Proliferation In Crpcmentioning
confidence: 99%
“…Lastly, ENO1 is a glycolytic enzyme that has been shown to contribute to proliferation, metastasis and therapy resistance through its role in glycolysis [45]. ENO1 is overexpressed and promotes tumor growth in head and neck, hepatocellular and gastric cancers [45]. Further interrogation of the DNA-PK/ENO1 interaction could expand our understanding of the role of DNA-PK in glycolysis and how these proteins together may impact response to therapy.…”
Section: Combination Of Dna-pk and Glycolysis Inhibitor Decreases Proliferation In Crpcmentioning
confidence: 99%
“…Over the years, several ENO1 inhibitors have performed promising results of the pharmacological-based study and preclinical trials (20,21). As the non-enzymatic active site inhibitor of ENO1, ENOblock reflects cytotoxicity in hypoxic and normal conditions on colon cancer cells (22). In addition, a series of enzymatic active inhibitors of ENO1, such as phosphonoacetohydroxamate acid (PhAH), (1,5-dihydroxy-2-oxopyrrolidin-3-yl)phosphonic acid (SF2312), deoxy-SF2312, Methyl-SF2312, POMSF, POMHEX and its derivatives, show potential anticancer in the functional cancer models (21,23).…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…As a glycolytic enzyme, ENO1 contributes to the Warburg effect and provides ATP to promote cancer development and progression [45]. In addition, ENO1 promotes the plasminogen activation system and upregulates integrin to enhance the migration and invasion of cancers [46][47][48]; ENO1 regulates gastric cancer cells stemness by stimulating glycolysis [49]. Our previous studies found that ENO1 promoted tumor proliferation, migration, and invasion in non-small cell lung cancer [50].…”
Section: Discussionmentioning
confidence: 99%